2021
DOI: 10.3390/medicina57050451
|View full text |Cite
|
Sign up to set email alerts
|

Drug Utilization for Pain Management during Perioperative Period of Total Knee Arthroplasty in China: A Retrospective Research Using Real-World Data

Abstract: Background and Objective: Total knee arthroplasty (TKA) is one of the most painful procedures and perioperative pain usually requires the use of many analgesics to relieve it. The appropriate use of analgesics to relieve patient pain is an important issue of TKA. To characterize the drug utilization for pain management during perioperative period of TKA in China using real-world data of electronic medical records. Materials and Methods: This research used the data of all inpatients who received TKA at 145 hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…With the aging of the population, degenerative diseases of joints are also increasing. Total knee arthroplasty (TKA) is a major technique for the treatment of severe knee joint disorders and the reconstruction of knee function, which can relieve knee pain and reconstruct knee function [ 1 ]. However, TKA is traumatic, and the patient's stress response is great, which often leads to severe postoperative pain, thus affecting the recovery of patients to some extent.…”
Section: Introductionmentioning
confidence: 99%
“…With the aging of the population, degenerative diseases of joints are also increasing. Total knee arthroplasty (TKA) is a major technique for the treatment of severe knee joint disorders and the reconstruction of knee function, which can relieve knee pain and reconstruct knee function [ 1 ]. However, TKA is traumatic, and the patient's stress response is great, which often leads to severe postoperative pain, thus affecting the recovery of patients to some extent.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al in their retrospective study observed that there were numerous postoperative usages of modes of analgesia for patients who have undergone TKA to control their pain. The type of operation, the level of surgery, the length of the surgery, and the anesthesia technique may all need to be taken into account when deciding whether to utilize analgesics [ 36 ]. Martin et al in their study stated that the post-operative healing following in total knee replacement has been revolutionized by the use of a combination of an efficient, technologically well-driven periarticular cocktail injection, a multimodal supplemental pain program, as well as the application of tranexamic acid to limit bleeding.…”
Section: Reviewmentioning
confidence: 99%